2017
DOI: 10.2527/jas2017.1674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot carcass weight on loin, ham, and belly quality from pigs sourced from a commercial processing facility1,2,3

Abstract: The objective was to determine the predictive abilities of HCW for loin, ham, and belly quality of 7,684 pigs with carcass weights ranging from 53.2 to 129.6 kg. Carcass composition, subjective loin quality, and ham face color were targeted on all carcasses, whereas in-plant instrumental loin color and belly quality were assessed on 52.0 and 47.5% of carcasses, respectively. Loin chop slice shear force (SSF), cured ham quality, and adipose iodine value (IV) were evaluated on at least 10% of the population. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Additionally, our findings contradict those of Harsh et al [ 43 ], who discovered that the color intensity of the longest back muscle increased ( p < 0.001) as pig pre-slaughter weight increased, but the pH declined ( p < 0.001). However, changes in pre-slaughter weight of only 1.23% resulted in statistically significant differences in pH.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, our findings contradict those of Harsh et al [ 43 ], who discovered that the color intensity of the longest back muscle increased ( p < 0.001) as pig pre-slaughter weight increased, but the pH declined ( p < 0.001). However, changes in pre-slaughter weight of only 1.23% resulted in statistically significant differences in pH.…”
Section: Discussioncontrasting
confidence: 99%
“…Several recent studies and market assessments have indicated that the weight of pork carcasses is expected to increase in upcoming years ( Morin et al, 2015 ; Harsh et al, 2017 ; Rice et al, 2018 ; Gilleland et al, 2019 ; Price et al, 2019 ). Harsh et al (2017) goes as far as to state predictions for carcass weights in the future, which were stated as 104 kg in 2030, 111 kg in 2040, and 118 kg in 2050. These predictions were based on the 0.6 kg/year increase that the United States pork carcass weights are currently experiencing ( USDA ERS, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported similar data with chops from heavier carcasses being more tender. 17,18 This could be due to the current industry chilling practices in which carcasses are chilled as quickly as possible to prevent pale, soft, and exudative (PSE) meat quality defects. Compared to the larger, heavier carcasses which cool slower, smaller carcasses chill at a faster rate.…”
Section: Resultsmentioning
confidence: 99%